Using Simulations in a One-to-One Computing Activity to Introduce Light Refraction Concepts - Ng, S.; Koh, T.; Treagust, David; Chandrasegaran, Arulsingam (Cambridge Publishing, 2012)
The study used a Flash simulation applet to facilitate understanding of basic refraction of light concepts among 31 Grade 8 secondary school physics students (14-year-olds) who were involved in a one-to-one laptop initiative. The students demonstrated satisfactory understanding of light refraction concepts, thereby supporting the use of the simulation applet while at the same time providing evidence of the strengths and shortcomings of the one-to-one laptop initiative.